English Language Training And Guiding For The Community-Based Tourism Group in Perean Village, Tabanan - Laksana, I Putu Yoga; Rahmanu, I Wayan Eka Dian (Jurnal Abdi Masyarakat, 2023)
The English and guiding training conducted in Perean Village aims to improve the language and guiding skills of the members of the Pokdarwis group. This is expected to enhance the quality and services of the village as a tourist destination that advances in the future. The community engagement activity was carried out by the community service team from the Language Lab Unit at Politeknik Negeri Bali for 5 months, consisting of 5 stages of activities from proposal to evaluation. In its implementation, the community service team provided various methods of English and guiding training and learning to the Pokdarwis participants, including interactive games, speaking, listening, and writing. Interactive games provide an opportunity for participants to learn English without feeling pressured, which positively impacts their motivation to learn consistently. Furthermore, the combination of speaking, listening, and writing training also has the potential to efficiently develop participants' skills, which is essential for tour guides who require good English skills. However, the weakness of participants in recognizing English vocabulary provides an opportunity for the community service team to develop a more specific approach in improving the vocabulary of the participants. This approach is expected to have a positive and significant impact in improving the English skills of tour guides in Perean Village, Tabanan, Bali.